AKTIVITAS TIM PROMOSI DAN MOTIVASI MAHASISWA (Studi Korelasi Antara Aktivitas Tim Promosi dengan Motivasi Mahasiswa Memilih Program Studi Ilmu Komunikasi di Universitas Slamet Riyadi Surakarta) - Dian Esti Nurati, Arya Dimar Putra Pujianto, Maya Sekar Wang & (Transformasi, 2015)
The results showed a positive and significant relationship between activity promotion team with motivated students choose Communication Studies Program at the University of Slamet Riyadi Surakarta on a significant level of 5% or 95% confidence level and rejection limits n-2 (38) = 1.684. Where the results of system level Spearman correlation of 0.591, after being tested with a (t) test result is 4.515 greater than the value of his criticism is 1.684 or 4.515> 1.684, then the hypothesis "There is a correlation between activity promotion team with motivation choose a course of Communication Sciences at the University Students Slamet Riyadi Surakarta "unacceptable. Keywords: Activity Promotion Team, and Student Motivation Choosing CommunicationStudies Program